2000
DOI: 10.1046/j.1365-2362.2000.0300s3034.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracrinology and the local enzymatic control of hormone distribution and metabolism: dehydroepiandrosterone does not just act as a prohormone for androgens and estrogens

Abstract: The study of subcellular environments for the interaction of biomolecules and observations of certain features of hormone actions have nourished the concept of 'intracrinology', which describes hormone actions within a singular cell, in contrast to the well-described autocrine, paracrine and endocrine fashion. Synthesis and metabolism of DHEA make it a likely candidate for intracrine actions in target tissues. Recent experimental findings are reviewed in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…DHEA is an important precursor for androgens and estrogens and members of the cytochrome P450, 3␤hydroxysteroid dehydrogenase, and 17␤-hydroxysteroid dehydrogenase enzyme families catalyze the various steps of sex steroid conversion (33,34). Enzymes required for converting DHEA into androgens and/or estrogens are expressed in a cell-specific manner in peripheral tissues (14,35), regulating the internal levels of androgens and estrogens in different cell populations and tissues. There is some evidence of direct effects of DHEA in cell-based assays, suggesting agonistic effects on ERs and antagonistic effects on the AR (17).…”
Section: Discussionmentioning
confidence: 99%
“…DHEA is an important precursor for androgens and estrogens and members of the cytochrome P450, 3␤hydroxysteroid dehydrogenase, and 17␤-hydroxysteroid dehydrogenase enzyme families catalyze the various steps of sex steroid conversion (33,34). Enzymes required for converting DHEA into androgens and/or estrogens are expressed in a cell-specific manner in peripheral tissues (14,35), regulating the internal levels of androgens and estrogens in different cell populations and tissues. There is some evidence of direct effects of DHEA in cell-based assays, suggesting agonistic effects on ERs and antagonistic effects on the AR (17).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, markedly elevated levels of DHEAS were found in NAF samples [39,[56][57][58], leading to the suggestion that DHEAS might serve within the breast as a precursor of the synthesis of testosterone, and subsequently of estrone and estradiol, according to in vitro studies demonstrating that breast tumor tissue, normal breast parenchyma and breast adipose tissue can convert DHEAS to testosterone, estrone and estradiol [59]. Moreover, the high concentrations of estrone sulfate and dehydro epiandrosterone found in NAF may serve as a reservoir for intracrine signaling.…”
Section: Androgensmentioning
confidence: 99%